Систематизація трансформаторно-ключових виконавчих структур перетворювачів напруги з ключовими елементами, що винесені з кіл силового струму - Липківський, К.О.; Можаровський, А.Г. (Технічна електродинаміка, 2011)
It is spent classification transformer switching executive structures the switch which have been taken out from chains of a power current. On a way of execution of the power autotransformer and the voltadding transformer these structures are divided into four groups, each of also is polyvariant. Possibility of transformation of structures of one group in structures of other groups is shown, recommendations about expedient use of separate variants are made. It is proved that the elementary structures of this class have full analogs in a class of structures with key elements in a chain of a power current.